PENGARUH UMPAN BALIK “SUKA” MEDIA SOSIAL (INSTAGRAM) TERHADAP HARGA DIRI INDIVIDU BERUSIA 20-39 TAHUN - Syalsa Maulina Sitompul; Free Dirga Dwatra (Universitas Negeri Padang, 2021)
Abstract: The impact.of social.media (Instagram) feedback “likes” on.self-esteem of 20-39 years old. Self-esteem possessed by individuals can be influenced by the feedback they get on selfies. One of the most social.media used to upload selfies, Instagram. “Like” feedback is one of the most factors that users want.iposts uploaded to social media. However, the number.of.likes can affect the user's self-esteem value. This study aims to see the effect of selfie upload feedback on the self-esteem value of female Instagram users. The purpose.of this.study was to find out the influence of social media